Captain America? On the relationship between Hollywood blockbusters and American soft power. Issue 1 (2nd January 2022) - Nelson, Travis
ABSTRACT: In 30 years, Hollywood movies have gone from making a majority of their money domestically to making a majority of their money internationally. This significant shift is underappreciated in scholarship such as International Relations research on soft power. This article argues that, counterintuitively, a growing global audience for Hollywood movies has diluted any soft power effect for the United States by globalizing their production and inducing content changes related to both setting and genre. In a globalized world, the connection between hard and soft power is more complicated than is traditionally understood.